Reading the unreadable. - Cherry, S.M.
The author discusses software tools that can recover data even from scratched and broken disks.
Keywords: CD/DVD Diagnostic; CD/DVD Inspector; Broken disks; Damaged disk; Data recovery tool; File recovery; Forensic scanning; Law enforcement agencies; Metadata; Scratched disks